Worn but not forgotten: the soviet shoes recycling in Ukraine in the - Tetiana Perga (Наукові записки Вінницького державного педагогічного університету імені Михайла Коцюбинського. Серія: Історія)
The aim of the article is to analyze the emergence of Soviet state policy on shoe recycling in the early 1930s, focusing on the Ukrainian SSR as a case study. Scientific novelty: While a growing body of literature addresses Soviet daily life, materiality, consumption, and repair practices, the area of shoe recycling remains underexplored at both the Union and Republican levels. Examining this niche aspect offers insight into the complexities of Soviet economic strategies and ideological narratives around resourcefulness, self-sufficiency and waste recycling. Research methodology: The study draws on previously unexplored Ukrainian archival materials, statistical collections of USSR and Soviet legislation, enabling a comprehensive and multi-dimensional analysis of the economic, social, and political implications of shoe recycling. The article also includes a comparative analysis of shoe recycling practices in the USSR and Germany during the 1920s and 1930s. This comparative angle sheds light on how both countries—facing resource scarcity and aim for self-sufficiency - leveraged recycling within their leather and footwear industries, albeit with differing ideological drivers and practices. Conclusions: In this article, it is argued that Soviet shoe recycling was more than just a practical response to resource scarcity; it was also ideologically motivated, aiming to demonstrate the advantages of the socialist system. The shoe recycling policy became an essential component of a broader waste reutilization strategy that began in the early 1920s. The so-called "shoe problem" served as a catalyst for advancements in science, technology, and alternative materials, as well as for the establishment of a state-led shoe repair program, a key element in the recycling process. At the same time, the ambitious plans of the Soviet government faced implementation challenges due to shortages in the Soviet economy.